The reconstruction of F. Kuršaitis syllable tones: initiation of new discusion - Švageris, Evaldas (Lietuvių kalba, 2016)
It is well known, that tones of Lithuanian language for the first time have been described and illustrated using musical notes in the mid of 19th century by Friedrich Kurschat (lt. Frydrichas Kuršaitis). No single attempt was made in order to analyze in-depth what specific prosodic features were covered by this material since the article of prof. A. Girdenis appeared in 2008. He concluded, that tone distribution is generally based on pitch range and contour differences (i.e. rising vs falling tone opposition). An alternative way of reconstruction proposed here reveals additional features which should be taken in to account as well. Measurements of prosodic parameters (i.e. pitch range, shape and vowel length) show that tones differ in terms of rate of pitch change and duration. Rising tone (or to be more precise – sustained tone)  can be defined as having longer duration and less intensive rate of pitch change while the falling tone has opposite parameters – shorter duration and abrupt, steep pitch change. The phonetic nature of Lithuanian language tones therefore should be considered as a complex one.
Keywords: syllable tone; reconstruction; pitch change; prosodic features; falling tone; rising tone